Nuclear service water piping : the Salem Nuclear Generating Station of the Public Service Electric & Gas Company, New Jersey, U.S.A. (Case study (Nickel Development Institute (Canada)) ;, 1995)
The Salem Nuclear Generating Station is located in the state of New Jersey on the east coast of the United States of America. It has two 1,100 MW operating units which went into service in 1977 and 1981. Despite regular inspection and maintenance of its service water system, both units began experiencing numerous problems with corrosion of the in-plant service water piping. This led the utility to thoroughly evaluate the problem and possible replacement materials and to conduct an extensive testing program. The results obtained from both the testing program and the plant's service experience with the various replacement materials are described in this case study.